2015
DOI: 10.1111/ajgw.12143
|View full text |Cite
|
Sign up to set email alerts
|

Effect of water deficit and severe shoot trimming on the composition ofVitis vinifera L. Merlot grapes and wines

Abstract: Background and Aims:In recent years, increasing summer temperature, coupled with reduced and erratic rainfall during the growing season, has induced accelerated fruit ripening in several regions, resulting in an undesirable increase in wine alcohol concentration. This study was designed to evaluate the impact of canopy and water management on grape sugar and flavonoid accumulation, with the goal of reducing wine alcohol concentration while conserving or enhancing the concentration of phenolic substances. Metho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

12
73
3
10

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 75 publications
(98 citation statements)
references
References 51 publications
12
73
3
10
Order By: Relevance
“…Article study in 'Merlot' indicated that even significant reductions of this ratio (from 1.5 to 1.0 m 2 /kg) do not have any significant effect on anthocyanin accumulation in the berry, 22 suggesting a lack of relationship between the LA/Y ratio and anthocyanin accumulation in this variety. Besides the total amount of anthocyanin, environmental cues, and viticultural practices can also affect the anthocyanin profile, i.e., the relative abundance of the different anthocyanins.…”
Section: Journal Of Agricultural and Food Chemistrymentioning
confidence: 91%
See 2 more Smart Citations
“…Article study in 'Merlot' indicated that even significant reductions of this ratio (from 1.5 to 1.0 m 2 /kg) do not have any significant effect on anthocyanin accumulation in the berry, 22 suggesting a lack of relationship between the LA/Y ratio and anthocyanin accumulation in this variety. Besides the total amount of anthocyanin, environmental cues, and viticultural practices can also affect the anthocyanin profile, i.e., the relative abundance of the different anthocyanins.…”
Section: Journal Of Agricultural and Food Chemistrymentioning
confidence: 91%
“…Sensory analyses of the wines were performed as described in Herrera et al 22 considering the following attributes: color (color intensity and hue), taste (acidity, bitterness, astringency, and minerality), aroma (intensity, fruity, herbaceous, and spicy), and…”
Section: ■ Materials and Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…13°13´E; elevation 88 m asl), in an 18-year-old Merlot vineyard grafted onto SO4 rootstock. The experimental site and design has been described in detail (Herrera et al 2015). Briefly, to maintain the vines under a fully controlled water regime, four 85 m-long rows were covered with an ethylene-vinyl-acetate film using a five m high, open-side tunnel structure.…”
Section: Methodsmentioning
confidence: 99%
“…Each treatment was replicated four times in experimental plots of 10 vines each in a completely randomized design. Vine water status was estimated weekly using midday measurements of Ψ stem as described (Herrera et al 2015).…”
Section: Methodsmentioning
confidence: 99%